Association of proteomic markers with nutritional risk and response to nutritional support: A secondary pilot study of the EFFORT trial using an untargeted proteomics approach. (April 2022) - Struja, Tristan; Laczko, Endre; Wolski, Witold; Schlapbach, Ralph; Mueller, Beat; Roschitzki, Bernd; Schuetz, Philipp
Summary: Background: By means of a structured nutritional support intervention, EFFORT showed a risk reduction for adverse events in medical in-patients. We were interested in the prognostic and therapeutic potential of an untargeted proteomics approach to understand response to nutritional support, risk of 30-day mortality, and distinct patterns in severity of malnutrition risk as assessed by the Nutritional Risk screening (NRS 2002), respectively. Methods: From 2, 088 patients, we randomly took 120 blood samples drawn before treatment initiation on day 1 after hospital admission. Cases were selected by treatment allocation (nutritional support vs. usual nutrition), NRS 2002, and mortality at 30 days, but not on disease type. We measured proteins by untargeted liquid chromatography mass spectrometry (LC-MS/MS). Results: We found 242 distinct proteins in 120 patients of which 81 (67.5%) survived until day 30. Between group analysis revealed a slight difference between the treatment groups in patients with a NRS 3, but not in those with a higher NRS. C-statistic between non-survivors and survivors at day 30 ranged from 0.60 (95% confidence interval 0.34–0.78) for a combination of 3 proteins/predictors to 0.65 (95% CI 0.53–0.78) for a combination of 32 proteins/predictors. In nutritional support non-survivors, pathway analysis found significant enrichment in pathways for signal transduction, platelet function, immune system regulation, extracellular matrix organization, and integrin cell surface interactions compared to survivors. Conclusion: Within this pilot study using an untargeted proteomics approach, there was only little prognostic and therapeutic potential of proteomics for phenotyping the risk of malnutrition and response to nutritional therapy. The small sample size and high heterogeneity of our population regarding comorbidity burden calls for more targeted approaches in more homogenous populations to understand the true potential of proteomics for individualizing nutritional care. Trial registration: This is a pre-planned secondary analysis of the EFFORT trial (ClinicalTrials.gov NCT02517476).